Hubungan Antara Hasil Seleksi Penerimaan Mahasiswa Baru ( Sipenmaru ) Motivasi Belajar dan Dukungan Keluarga Dengan Prestasi Belajar Mahasiswa Di Akademi Keperawatan PPNI Surakarta - Joko Waluyo, Sunaryo; -, Sugiyarto (Intan Husada : Jurnal Ilmiah Keperawatan, 2015)
Background:  quality  health  services,  to  be  supported  by  qualified health personnel, quality health indicators one of which  is the achievement of academic achievement. Implementation Sipenmaru standards that have been set, motivation and  family  support  affect  the  achievement  of  student learning. Methods:  This  study  is  a descriptive correlational cross-sectional study design. Sampling technique with random  sampling sample  of 75 students AKPER PPNI Semester IV. Primary data on,  motivation, family support  and students' learning is  obtained from  the questionnaires,  data  Sipenmaru of documentation and  data values  Sipenmaru  results  obtained    from  the learning  achievement  evaluation throught ests mid semester IV. Results:  The  results  of  the  multiple  correlation  analys  is  of  the independent variable values Sipenmaru (X1), motivation (X2) and family support (X3) on the dependent  variable  learning  achievement  (Y)  obtained results  R  (correlation coefficient)  0.916,  multiple  regression  test  results obtained  values  F count=124.046 and F table =3124 and a significance value of 0000, F (124.046) > F table(3124)  and Sig.0.000<0.05. Effective contribution (R2)  /R Square : 0.840 jointly acquired. Conclusion:  There  is  a strong  positive  relationshipand  significant  correlation between  interest  and motivation  toward  achievement  of  students  in  Nursing Academy PPNI Surakarta.  Keywords: Sipenmaru,  Motivation, Family support,Learning Achievement